Obecność zarodników grzybów pleśniowych w nalocie na elewacji budynku Insystutu Inżynierii Środowiska Uniwersytutu Zielonogórskiego = Existence of mould spores in biofilm on the building fasade of the Institute of Environmental Engineering, University of Zielona Góra - Piontek, Marlena; Lechów, Hanna; Łuszczyńska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this study was to estimate the qualitative diversity of mould spores on the biofilm that has grown on the western facade of the building of the Institute of Environmental Engineering, University of Zielona Góra. Scientific literature describes instances where mould spores lead and contribute to the process of biodegradation of technical materials. A part of the material was subjected to analysis performed with the use of an scanning electron microscope.
Keywords: grzyby pleśniowe; biokorozja; biodeterioracja; nalot biologiczny; elewacje zewnętrzne; moulds; fungi; biocorrosion; biodeterioration; biofilm; exterior facades